Role of Modern Teaching Approaches in Drought and Water Distribution on Earth in Students’ Learning in Social Studies at Grade-VIII: An Analysis - Abdul Sattar Pitafi; Dr. Jam Muhammad Zafar (Research Journal of Psychology, 2025)
The study aimed to analyze the, “Role of Modern Teaching Approaches in Drought and Water Distribution on Earth on Students’ Learning in Social Studies at Grade-VIII: An Analysis”. Objectives of the study were to analyze the role of modern teaching approaches in Social Studies on students’ learning at Grade-VIII. This survey-based study utilized both quantitative and qualitative methods (QUAN-qual.), with a sample consisting of 20 Head Master, 60 Junior Elementary School Teachers, and 320 Elementary school children - for a total sample size of 400 individuals. The researchers followed L.R.GAY’s sampling chart when selecting participants. Research tools included questionnaires based on three parts: Part-1 Demographic; Part-2 Closed-ended; and part-three Open-ended questions from sampled Head Master & JESTs .Additionally an observation sheet was used for data collection specific to Elementary class children. To ensure validity & reliability all research tools underwent pilot testing as well ensuring their accuracy through expert opinion while also having using Cronbach Alpha calculations to test questionnaire reliability. SPSS-24 statistical software was employed during analysis which involved utilizing relevant formulas such frequency measurement percentage measures standard deviation etc.